Management of textile wastewater for improving growth and yield of field mustard (Brassica campestris L.). Issue 9 (2nd September 2017) - Yaseen, Muhammad; Aziz, Muhammad Zahir; Komal, Aqleema; Naveed, Muhammad
ABSTRACT: Disposal of industrial wastewater is a current issue of urbanization. However, this problem can be sorted out by using wastewater as an alternate source of irrigation after the addition of some amendment. In this way, the problem of disposal of wastewater not only will be resolved but also scarcity of irrigation water can be kept off in the future. The current research study was performed to evaluate the influence of different concentrations of wastewater along with canal water for enhancing growth and yield of field mustard. Plants were irrigated with different mixtures of canal water and wastewater (75:25, 50:50, 25:75, and 00:100) in addition to canal water as control. The results revealed that application of 50:50% waste and canal water improved plant height, the number of pods plant −1, pod length, root length, root dry weight, shoot dry weight, 100 grain weight, grain and biomass yield plant −1, and nitrogen, phosphorus, and potassium concentration in grain and straw up to 16%, 15%, 17%, 29%, 15%, 56%, 25%, 41%, 35%, 20%, 52%, 45%, 20%, 44%, and 42%, respectively, over positive control treatment. While, nutrient uptakes and agronomic efficiency of fertilizers also improved by the application of 50:50% canal and wastewater compared to positive control treatment. Furthermore, the concentration of heavy metals, predominantly Cr, Cu, Cd, and Pb, was reduced in grains by application of 50% canal water and 50% wastewater. The outcomes suggest that wastewater utilization along with canal water mixing might be an effective approach for enhancing growth and yield of field mustard.